Effects of selective serotonin reuptake inhibitors and other antidepressant drugs on the risk of hip fracture: a case–control study in an elderly Mediterranean population. Issue 1 (20th May 2019) - Gorgas, Maria Queralt; Torres, Ferran; Vives, Roser; Lopez-Rico, Irene; Capella, Dolors; Pontes, Caridad
Abstract : Objectives: To describe the association between exposure to different antidepressant drugs and hip fracture in an elderly Mediterranean population. Methods: Cases were all patients aged 50–95 years admitted to the emergency room of our hospital with hip fracture not related to a high intensity trauma during 2010. For each case, four controls were identified from primary care electronic medical records matched by age (±3 years), gender, date of consultation at the primary care centre (±1 month) and primary care centre. Pharmacological treatments received within the previous 5 years were retrieved from the prescription records. Crude and adjusted risks associated with exposures were calculated by conditional logistic regression. ORs were adjusted by matching variables and by significant risk factors identified in the bivariate analysis (prescription of ≥4 drugs, osteoporosis, diabetes mellitus and previous fracture). Results: 136 cases and 544 controls were analysed. Adjusted OR (95% CI) for hip fracture associated with exposure to any antidepressants was 2.42 (1.24 to 4.73); for selective serotonin reuptake inhibitors (SSRIs) it was 3.52 (1.67 to 7.41), for non-selective monoamine reuptake inhibitors 1.07 (0.18 to 6.46) and for other antidepressants 0.82 (0.27 to 2.48). Sertraline (OR 3.88 (1.15 to 13.09)) was the only active principle with significant adjusted risk. When only exposures >6 months were considered, significant risks persisted for SSRIs (OR 2.64 (1.10 to 6.37)). Conclusions: The results of this study are coincident with other studies in which SSRIs, but not other types of antidepressants, are associated with an increased risk of hip fracture in our setting.